COMPATIBILITY OF SOME ADHESIVES WITH BATANG RATTAN (Calamus zollingeri Becc.) AS RAW MATERIAL OF RATTAN LAMINATED BOARD - Adi Santoso; Ignasia M. Sulastiningsih; Rohmah Pari (Indonesian Journal of Forestry Research, 2022)
Rattan in Indonesia is traditionally utilized for furniture, binding materials, household appliances, and handicraft items. Small diameter rattans are commonly used by craftsmen, while large diameter rattans are not optimally utilized. Large diameter rattan, however, has potential to be developed into rattan laminated board (RLB) by gluing rattan strips using appropriate adhesive. Nevertheless, the information of the suitable natural adhesive for RLB production is still limited. Laboratory scale of RLBs with the dimensions of 60 cm x 7.5 cm x 1.5 cm were manufactured using batang rattan strips (Calamus zollingeri Becc.). The strips were glued with six types of adhesives (4 types of natural adhesives and 2 types of commercial synthetic adhesives) and three glue spread rates of (100, 150, and 200 g/m2) were used. The study objective was to determine the effect of rattan pre-treatments, adhesive types and glue spread rates on the bonding quality and formaldehyde emission of RLBs. The results showed that batang rattan can be processed into RLBs by using natural adhesives originating from wood bark extract (mangium, mahogany), merbau wood powder, as well as commercial synthetic adhesives such as isocyanate and polyurethane. The appropriate pre-treatment in producing RLBs for interior furniture was by applying oil heat treatment with kerosene solution (80 kerosene : 20 water) and glued with tannin adhesive of mangium bark extract with glue spread of 200 g/m2. Similarly, rattan strips treated with heated oil (80 kerosene : 20 water) and glued with polyurethane adhesive (glue spread of 200 g/m2) produced excellent RLBs for exterior furniture.